Status of Nuclear Security Education and Research in Bangladesh and Looking Forward - Md. Shafiqul Islam; Md. Mobasher Ahmed (International Journal of Nuclear Security, 2016)
Bangladesh uses category I of nuclear materials and category 1-5 of radioactive materials in the field of research, medical and industries. The Government is going to implement its first nuclear power plant under an IGA between the Bangladesh and Russian Governments. With the emerging global nuclear and radiological terrorism by potential adversaries, enhancing nuclear security is the paramount importance for the country. The paper has found no established communication channels among stakeholders in order to work in a coordinated and collaborative manner for strengthening the nuclear security. This has resulted lacking importance of education, research, training and knowledge management initiatives among stakeholders. Developing nuclear security policy at national and organizational levels, regulatory documents, technical guidance and action plan are also lacking. The paper suggests for creating a powerful nuclear security governance to collectively tackle the nuclear insecurity dynamics. This paper also suggests for establishing an institution under a public university with a global partnership for enhancing and sustainable maintaining the nuclear security regime through developing competent human resources.
Keywords: Nuclear Security; Education; Research; Governance; Enhancement.